MODEL FOR IMPLEMENTATION OF THE ACEH TRADITIONAL ASSEMBLY DEVELOPMENT IN WINNING TRADITION IN ACEH TAMIANG - Syafrizal Syafrizal (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
Marriage customs for the Tamiang tribe are a powerful